Estimation of Spectral Exponent Parameter of 1/f Process in Additive White Background Noise. (17th June 2007) - Baykut Baykut, Süleyman Süleyman; Akgül Akgül, Tayfun Tayfun; Ergintav Ergintav, Semih Semih
Abstract : An extension to the wavelet-based method for the estimation of the spectral exponent, γ, in a1 / f γ process and in the presence of additive white noise is proposed. The approach is based on eliminating the effect of white noise by a simple difference operation constructed on the wavelet spectrum. Theγ parameter is estimated as the slope of a linear function. It is shown by simulations that the proposed method gives reliable results. Global positioning system (GPS) time-series noise is analyzed and the results provide experimental verification of the proposed method.